2014
DOI: 10.1088/0741-3335/57/1/014030
|View full text |Cite
|
Sign up to set email alerts
|

Advanced scheme for high-yield laser driven nuclear reactions

Abstract: The use of a low contrast nanosecond laser pulse with relatively low intensity (3 × 10 16 W cm -2 ) allowed enhancing the yield of induced nuclear reactions in advanced solid targets. In particular the "ultraclean" proton-boron fusion reaction, producing energetic alpha-particles without neutron generation, was chosen. A spatially well-defined layer of boron dopants in a hydrogenenriched silicon substrate was used as target. The combination of the specific target geometry and the laser pulse temporal shape all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 35 publications
(41 reference statements)
4
73
1
Order By: Relevance
“…Combining the experimental result of most exceptionally high gains of proton-boron (HB11) fusion Picciotto et al, 2014;Margarone et al, 2015) based on the concluded avalanche mechanisms (Hora et al,. 2014b;2015) and evaluated now in more details, with the results of >PW-ps laser-driven block ignition (Hora et al, 2010;Lalousis et al, 2014) was leading to a first step of producing ultraclean GJ fusion energy possibly by 30 kJ laser irradiation.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Combining the experimental result of most exceptionally high gains of proton-boron (HB11) fusion Picciotto et al, 2014;Margarone et al, 2015) based on the concluded avalanche mechanisms (Hora et al,. 2014b;2015) and evaluated now in more details, with the results of >PW-ps laser-driven block ignition (Hora et al, 2010;Lalousis et al, 2014) was leading to a first step of producing ultraclean GJ fusion energy possibly by 30 kJ laser irradiation.…”
Section: Discussionmentioning
confidence: 97%
“…A convincing and very transparent result (Labaune et al, 2013) produced more than 10 6 reactions though only a complicated combination of laser-driven directed particle beams with a secondary laser-target interaction was used. After this breakthrough, the measurement of 10 9 /sr reactions Margarone et al, 2015) was achieved. These measurements were a straightforward laser-fusion result by a unique combination of one of the largest European lasers, the PALS iodine laser at Prague, with the use of a very unusual laser-irradiated target.…”
Section: Very High Boron Fusion Explained As Avalanche Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] In the last decade a renewed interest on this topic has been shown through the possibility to trigger such nuclear reactions by using high power pulsed laser interacting with solid B-enriched targets. [10][11][12][13][14][15][16][17] Charged energetic particles are routinely used in medicine, in particular in cancer therapy. Currently hadron-therapy is becoming one of the most important medical procedures to treat solidified tumors instead of traditional radiotherapy treatments.…”
Section: Introductionmentioning
confidence: 99%